Synthesis of amphiphilic poly(methyl methacrylate-b-ethylene oxide) copolymers from monohydroxy telechelic poly(methyl methacrylate) as macroinitiator - Dhara, Mahua Ganguly; Baskaran, Durairaj; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2008)
The synthesis of well-defined poly(methyl methacrylate)-block-poly(ethylene oxide) (PMMA-b-PEO) dibock copolymer through anionic polymerization using monohydroxy telechelic PMMA as macroinitiator is described. Living anionic polymerization of methyl methacrylate was performed using initiators derived from the adduct of diphenylethylene and a suitable alkyllithium, either of which contains a hydroxyl group protected with tert-butyldimethylsilyl moiety in tetrahydrofuran (THF) at -78 degrees C in the presence of LiClO4. The synthesized telechelic PMMAs had good control of molecular weight with narrow molecular weight distribution (MWD). The H-1 NMR and MALDI-TOF MS analysis confirmed quantitative functionalization of chain-ends. Block copolymerization of ethylene oxide was carried out using the terminal hydroxyl group of PMMA as initiator in the presence of potassium counter ion in THF at 35 degrees C. The PMMA-b-PEO diblock copolymers had moderate control of molecular weight with narrow MWD. The H-1 NMR results confirm the absence of trans-esterification reaction of propagating PEO anions onto the ester pendants of PMMA. The micellation behavior of PMMA-b-PEO diblock copolymer was examined in water using H-1 NMR and dynamic light scattering. (C) 2008 Wiley Periodicals, Inc.
Keywords: Anionic polymerization; block copolymers; synthesis

Synthesis of hydroxy-functional PMMA macromonomers by anionic polymerization - Dhara, Mahua Ganguly; Sivaram, Swaminathan; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2009)
Living anionic polymerization has been utilized to synthesize hydroxy end-functionalized PMMA macromonomers with styryl or allyl functionalities as the polymerizable end-groups. Protected hydroxy-functionalized alkyl lithium initiators have been used to initiate anionic polymerization of MMA. Subsequently the living chains with protected hydroxyl function have been terminated using 4-vinylbenzyl chloride (4-VBC) or allyl methacrylate (ALMA) to form -hydroxy–styryl and -hydroxy–allyl PMMA, respectively. These protected hydroxy-functionalized PMMA macromonomers have been characterized by GPC and 1H-NMR. Termination using 4-VBC led to 50% functionalization, whereas that using allyl methacrylate led to 100% functionalization of the hydroxy-PMMA.
Keywords: Anionic polymerization; functionalized initiator; Macromonomer

Synthesis of hydroxy-functionalized star-branched PMMA by anionic polymerization - Dhara, Mahua Ganguly; Sivaram, Swaminathan; Baskaran, Durairaj (Polymer Bulletin, 2009)
Living anionic polymerization has been exploited to synthesize hydroxy end-functionalized PMMA star-branched polymers. Protected hydroxy-functionalized alkyl lithium initiators have been used to initiate anionic polymerization of MMA. Subsequently the living chains with protected hydroxyl function have been used to cross-link ethylene glycol dimethacrylate (EGDMA) in order to form star-branched polymers with cross-linked EGDMA core via `arm-first' method. The linear arms and the star molecules have been characterized by (1)HNMR, GPC, and light scattering. Variation in the number of arms with arm molecular weight and cross-linker loading has been studied. Star-branched PMMA-OH with as many as similar to 10 arms could be successfully made. Increased molecular weight of PMMA-OH led to decrease in the number of arms incorporated due to increased steric hindrance on the core. Increase in EGDMA concentration slightly increased the arm incorporation.
Keywords: Anionic polymerization; Star polymers; Star-branched PMMA